2017
DOI: 10.3389/fimmu.2017.01736
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Human Natural Killer Cell Response at Single-Cell Resolution in B-Cell Non-Hodgkin Lymphoma

Abstract: Natural killer (NK) cells are phenotypically and functionally diverse lymphocytes that recognize and kill cancer cells. The susceptibility of target cancer cells to NK cell-mediated cytotoxicity depends on the strength and balance of regulatory (activating/inhibitory) ligands expressed on target cell surface. We performed gene expression arrays to determine patterns of NK cell ligands associated with B-cell non-Hodgkin lymphoma (b-NHL). Microarray analyses revealed significant upregulation of a multitude of NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 71 publications
0
61
0
Order By: Relevance
“…CD19 antigen density were determined by flow cytometry, using Quantibrite anti-CD19-PE (Clone SJ25C1)#340364, and Quantibrite-PE calibration beads (BD Bioscience, San Jose, CA, USA). Primary human lymphoma cells (EL-2 and EL-5) were isolated from IRB exempt discarded tissue specimens of patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) obtained through Tufts Tumor Repository, as described previously [17]. Activated NK-92 (aNK) and CD19.CAR.NK92 cells were provided as gift from Nantkwest, Inc. (Woburn, MA, USA) and the details of CAR construct used in design and development of CD19.CAR.NK92 cells is outlined in [1,2], and (Supplemental Methods).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…CD19 antigen density were determined by flow cytometry, using Quantibrite anti-CD19-PE (Clone SJ25C1)#340364, and Quantibrite-PE calibration beads (BD Bioscience, San Jose, CA, USA). Primary human lymphoma cells (EL-2 and EL-5) were isolated from IRB exempt discarded tissue specimens of patients with relapsed/refractory diffuse large B-cell lymphoma (DLBCL) obtained through Tufts Tumor Repository, as described previously [17]. Activated NK-92 (aNK) and CD19.CAR.NK92 cells were provided as gift from Nantkwest, Inc. (Woburn, MA, USA) and the details of CAR construct used in design and development of CD19.CAR.NK92 cells is outlined in [1,2], and (Supplemental Methods).…”
Section: Cell Culturementioning
confidence: 99%
“…Target cells labeled with 2μM Calcein AM (Thermo Fisher, Waltham, MA; excitation/ emission: 495nm/515nm) at 37°C for 20 minutes, were washed once with media and loaded in a syringe at 1.5 million/mL concentration. Both target cells and unlabeled CD19.CAR.NK92 were introduced in the microfluidic device, oil droplets were generated and image acquisition were performed as outlined before [17]. Target cell death was indicated by significant (>80%) loss of Calcein AM fluorescence, number of contacts made and duration of contacts between cell pairs were determined as described previously [17,22].…”
Section: Microfluidic Analysismentioning
confidence: 99%
“…Their results suggested that the activation of single T-cells is faster when cells come in contact with dendritic cells in comparison to other activation methods. Furthermore, they developed a method to probe into the potentially heterogeneous cytolytic behavior of human NK cells ( 162 ). They demonstrated a 100% killing efficiency of NK cells, which is in contrast to earlier findings by various groups performed either in bulk or single cell ( 105 , 163 ).…”
Section: Introduction: Immunoengineeringmentioning
confidence: 99%
“…The Voldman's group has published a series of works regarding pairing cells using hydrodynamic traps, which allowed the deterministic control of the initiation of cell-cell interactions, including CTL and the antigen-presenting cells 50,51 . Sarkar et al probed the cytolytic activities of individual NK cells coencapsulated with lymphoma cells in picoliter droplets generated by a microfluidic device 52 and demonstrated that a higher efficiency of the derivative NK cell line NK-92 in eradication of primary B-cell non-Hodgkin lymphoma cells than the primary NK cells. Christakou et al examined the variation of one hundred NK-mediated cytolysis against major histocompatibility complex class (MHC) I-deficient tumor cells in parallel by utilizing ultrasound to synchronize the contacts between the two types of cells in a multiwell chip 53 .…”
Section: Discussionmentioning
confidence: 99%